Impact of metallurgical factors on the resistance of working ladle lining - Kovalenko, А.G.; Riaby, D.V.; Smirnov, А.N.; Kondrukevich, A.А.; Semiriagin, S.V.; Strichenko, S.M. (Металл и литье Украины, 2016)
This article examines the impact of main metallurgical factors on the stability of the working lining of steel ladles for plant that smelts low-alloy, carbon and low silicate assortment with turnover of more than 4,5 ladle heats/day, shares of heats processed on the ladle furnace – 100% and casting on continuous casting machine by open stream. By results of work the determinants factors and their share of influence on the stability of steel ladle have been estimated. В статье рассмотрено влияние основных металлургических факторов на стойкость рабочей футеровки сталеразливочных ковшей для завода, выплавляющего низколегированный, углеродистый и низкокремнистый сортамент с оборачиваемостью стальковша более 4,5 плавок/сутки, долей плавок обрабатываемых на установке «ковш-печь» (УКП) – 100% и разливкой на машине непрерывного литья заготовок (МНЛЗ) открытой струей. По результатам работы оценены определяющие факторы и их доля влияния на стойкость стальковша. У статті розглянуто вплив основних металургійних факторів на стійкість робочої футерівки сталерозливних ковшів для заводу, який виплавляє низьколегований, вуглецевий і низькокремнистий сортамент з оборотністю стальківша понад 4,5 плавок/добу, часткою плавок, що обробляються на установці «ківш-пічь» (УКП) – 100% і розливанням на машині неперервного лиття заготовок (МБЛЗ) відкритим струменем. За результатами роботи оцінено визначальні чинники і їх частку впливу на стійкість стальківша.